Strategic Leadership in Education: Navigating Change in Digital Learning Environments - Baharuddin, Baharuddin; Sembiring, Harianta; Astuti, Andri; Tshabalala, Zanele (International Journal of Educational Narratives, 2024)
The rapid advancement of digital technologies has significantly transformed the educational landscape, requiring educational leaders to adopt strategic leadership approaches that can effectively navigate change in digital learning environments. As schools and universities increasingly integrate technology into their instructional practices, the need for leaders who can guide these transitions and foster a culture of innovation has become critical. This study aims to explore the role of strategic leadership in managing and implementing change within digital learning environments. It seeks to understand how educational leaders can facilitate the adoption of digital technologies, create a supportive learning culture, and ensure the effectiveness of digital learning initiatives. A qualitative research design was employed, utilizing case studies and interviews with educational leaders from various educational institutions. Data were collected from 20 leaders, including principals, deans, and administrators, to gain insights into their strategies for navigating digital transformation. Thematic analysis was used to identify key strategies and challenges in digital leadership. The findings highlight several key strategies employed by leaders, including fostering collaboration, investing in professional development, and creating a shared vision for digital transformation. However, challenges such as resistance to change, lack of resources, and insufficient training were also identified as barriers to successful implementation. The study concludes that strategic leadership is essential for navigating the complexities of digital transformation in education. Educational leaders must adopt adaptive leadership styles, focus on continuous learning, and leverage technology to enhance teaching and learning processes. Institutions that prioritize strategic leadership will be better positioned to thrive in the digital era.